Pengawasan Atasan Langsung di lembaga Penjamin Mutu Pendidikan Provinsi Sumatra Barat - Muhammad Rasyidi; Sulastri Sulastri; Jasrial Jasrial; Nelitawati Nelitawati (Journal of Educational Administration and Leadership, 2021)
This research is based on the observations of the authors at the Office of the Quality Assurance Agency for Education of West Sumatra Province regarding the supervision of direct superiors that are still not well implemented. This research aims to obtain information on Direct Supervisory Supervision at the Education Quality Assurance Agency of West Sumatra Province as seen from the indicators of supervision procedures, supervision techniques, supervisory time and follow-up supervision. This research is descriptive with quantitative methods. The population of this research is employees in the Education Quality Assurance Agency of West Sumatra Province amounting to 76 employees, the sample taken is a population research so that the number of 76 respondents or all subjects in this study. Data collected using questionnaires. The average formulation is used in processing data in this research Data shows that direct supervisory supervision namely: (1) Supervision procedures get a score with an average of 4.26 fall into the good category; (2) Surveillance Techniques get a score with an average of 4.02 fall into the good category; (3) Supervised time scores with an average of 4.08 fall into the good category; (4) Follow-up supervision gets a score with an average of 3.66 belongs to the good category. Overall, Direct Supervisory Supervision at the Education Quality Assurance Agency of West Sumatra Province scored with an average of 4.00 in the good category.